Investigating The Effect of Teaching EFT Technique on Reducing Anxiety of Nurses During Corona Outbreak - Rostami , Khatereh; Azita Tiznobaik; Maleki , Leila; Maryam; Taheri, Narjes Khaton (International Journal of Psychosocial Rehabilitation, 2020)
Corona virus is a family of viruses that can cause a wide range of diseases. Nurses are among those who have to attend hospital settings due to their job nature and are exposed to suspected patients with Corona. so they experience high level of stress and anxiety. The "Emotional Freedom Technique" (EFT) is an alternative treatment for removing physical pain and emotional distress.This study was conducted to investigate the effect of using EFT on anxiety of nurses during Corona outbreak.The present study was a clinical trial. The statistical population of the present study included all nurses working in hospitals. The data collection tool consisted of two sections: demographic information and the Nursing Stress Scale NSS developed by Gray-Toft James Anderson. After entering the data into computer, they were analyzed through SPSS24 software and by paired T-tests and analysis of variance with repeated observations. It should be noted that the significance level of the study was considered at P